Effects of a plyometrics intervention program on sprint performance - Rimmer, E.; Sleivert, G. (The Journal of Strength and Conditioning Research, 2000)
To determine the effects of a sprint-specific plyometrics program on sprint performance, an 8-week training study consisting of 15 training sessions was conducted. Twenty-six male subjects completed the training. A plyometrics group (N = 10) performed print-specific plyometric exercises, while a sprint group (N = 7) performed sprints. A control group (N = 9) was included. Subjects performed sprints over 10- and 40-m distances before (Pre) and after (Post) training. For the plyometrics group, significant decreases in times occurred over the 0-10-m (Pre 1.96 ± 0.10 seconds, Post 1.91 ± 0.08 seconds, p = 0.001) and 0-40-m (Pre = 5.63 ± 0.18 seconds, Post = 5.53 ± 0.20 seconds, p = 0.001) distances, but the improvements in the sprint group were not significant over either the 0-10-m (Pre 1.95 ± 0.06 seconds, Post 1.93 ± 0.05 seconds) or 0-40-m distance (Pre 5.62 ± 0.14 seconds, Post 5.55 ± 0.10 seconds). The magnitude of the improvements in the plyometrics group was, however, not significantly different from the sprint group. The control group showed no changes in sprint times. There were no significant changes in stride length or frequency, but ground contact time decreased at 37 m by 4.4% in the plyometrics group only. It is concluded that a sprint-specific plyometrics program can improve 40-m sprint performance to the same extent as standard sprint training, possibly by shortening ground contact time.